3D Cartesian MRI with compressed sensing and variable view sharing using complementary poisson‐disc sampling. Issue 5 (21st April 2016) - Levine, Evan; Daniel, Bruce; Vasanawala, Shreyas; Hargreaves, Brian; Saranathan, Manojkumar
Abstract : Purpose: To enable robust, high spatio‐temporal‐resolution three‐dimensional Cartesian MRI using a scheme incorporating a novel variable density random k‐space sampling trajectory allowing flexible and retrospective selection of the temporal footprint with compressed sensing (CS). Methods: A complementary Poisson‐disc k‐space sampling trajectory was designed to allow view sharing and varying combinations of reduced view sharing with CS from the same prospective acquisition. These schemes were used for two‐point Dixon‐based dynamic contrast‐enhanced MRI (DCE‐MRI) of the breast and abdomen. Results were validated in vivo with a novel approach using variable‐flip‐angle data, which was retrospectively accelerated using the same methods but offered a ground truth. Results: In breast DCE‐MRI, the temporal footprint could be reduced 2.3‐fold retrospectively without introducing noticeable artifacts, improving depiction of rapidly enhancing lesions. Further, experiments with variable‐flip‐angle data showed that reducing view sharing improved accuracy in reconstruction and T1 mapping. In abdominal MRI, 2.3‐fold and 3.6‐fold reductions in temporal footprint allowed reduced motion artifacts. Conclusion: The complementary‐Poisson‐disc k‐space sampling trajectory allowed a retrospective spatiotemporal resolution tradeoff using CS and view sharing, imparting robustness to motion and contrast enhancement. The technique was also validated using a novel approach of fully acquired variable‐flip‐angle acquisition. Magn Reson Med 77:1774–1785, 2017. © 2016 International Society for Magnetic Resonance in Medicine